Financial markets and monetary control under high inflation: The case of Argentina - Bernhard Fischer; Peter Trapp (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1985)
Argentina's economic development over the last thirty years has been dominated by very high and variable inflation rates. There is widespread agreement that the financial sector is most seriously affected by persistent inflation. This was also true for Argentina. Due to interest rate ceilings and other regulations relative yields on particular financial assets have been affected differently by inflation. While the holdings of non-interest bearing assets (currency in circulation and demand deposits) were fully exposed to the inflation tax , time deposits at a controlled rate or indexed deposits were partially protected from inflation losses, however, at varying degrees. As a consequence there was a tendency to substitute money in circulation and demand deposits for interest-bearing, short-term assets.
Keywords: 330